2011
DOI: 10.1242/jeb.046292
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the elusive peptidergic diuretic hormone in the blood-feeding bugRhodnius prolixus: a CRF-related peptide

Abstract: SUMMARYProbing of a host and ingestion of a blood-meal in a fifth instar Rhodnius prolixus results in a cascade of tightly integrated events. The huge blood-meal is pumped into the anterior midgut during feeding, then modified by diuresis and stored until it is digested. While serotonin is known to be a diuretic hormone in R. prolixus, a peptidergic factor(s) was also known to play a role in diuresis. In the present study we employed molecular techniques and mass spectrometry to determine the sequence of a nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(24 citation statements)
references
References 60 publications
2
22
0
Order By: Relevance
“…Although other DHs are present in insects, the two most studied are calcitonin-like and corticotropin releasing factor-like diuretic hormone (CT/DH and CRF/DH), which both stimulate the secretion of water in the Malpighian tubules (reviewed in [64,65]). Besides diuresis, they appear to have roles in feeding behavior [66,67]. We detected DH peptides in the TG and the brain.…”
Section: Diuretic Hormones -Ion Transport Peptidementioning
confidence: 77%
“…Although other DHs are present in insects, the two most studied are calcitonin-like and corticotropin releasing factor-like diuretic hormone (CT/DH and CRF/DH), which both stimulate the secretion of water in the Malpighian tubules (reviewed in [64,65]). Besides diuresis, they appear to have roles in feeding behavior [66,67]. We detected DH peptides in the TG and the brain.…”
Section: Diuretic Hormones -Ion Transport Peptidementioning
confidence: 77%
“…The full boxes indicate the CRF-like DH coding region, flanked by dibasic cleavage sites (“(G)KR”). Abbreviations: Apime -DHP, Apis mellifera CRF-like DH precursor [16]; Harsa -DHP, Harpegnathos saltator CRF-like DH precursor (UniProtKB/TrEMBL: E2B7W2); Schgr -DHP, S. gregaria OMP-DH-L precursor (described in this paper); Rhopr -DHP, Rhodnius prolixus CRF-like DH precursor [5], UniProtKB/TrEMBL: F1AYR6; Trica -DHP, Tribolium castaneum CRF-like DH (47) precursor [17]. B) Alignment of the CRF-like peptides and OMPs from Schistocerca gregaria ( Schgr -DH and Schgr -OMP) and Locusta migratoria ( Locmi -CRF/DH and Locmi -OMP).…”
Section: Resultsmentioning
confidence: 99%
“…In many insect species, a diuretic hormone (DH) related to the vertebrate Corticotropin Releasing-Factor (CRF) has been characterized [1]. This CRF-like DH (CRF/DH) was first identified in the moth, Manduca sexta [2], but has now also been isolated and characterized in diverse insect species, such as the beetle Tenebrio molitor [3], the termite Zootermopsis nevadensis [4], the kissing bug Rhodnius prolixus [5] and the locust Locusta migratoria [6], [7]. In addition to its role in stimulating diuresis, the CRF-like DH was also suggested to be involved in the mediation of satiety in L. migratoria , since injection of this locust neuropeptide ( Locmi -CRF/DH) influenced the duration of the meal and the latency to feed [8], [9].…”
Section: Introductionmentioning
confidence: 99%
“…The gene has now been cloned, but in only a small number of insect species, including D. melanogaster , D. pseudoobscura , T. castaneum , A. pisum , and now R . prolixus (Taylor et al, 2004; Hauser et al, 2008; Weaver and Audsley, 2008; Huybrechts et al, 2010). Recently, the first non-insect arthropod proctolin genes were reported in the Pacific white shrimp, L. vannamei , and the water flea, D. pulex (Ma et al, 2010; Dircksen et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The genes for proctolin and its receptor were, however, eventually identified and cloned in D. melanogaster (Egerod et al, 2003; Johnson et al, 2003a,b; Taylor et al, 2004), although surprisingly, proctolin has not been chemically identified in D. melanogaster (see Nässel and Winther, 2010). Subsequently, the proctolin gene was found in the genomes of only a few insect species, including Tribolium castaneum, Tenebrio molitor , and Acyrthosiphon pisum (Hauser et al, 2008; Li et al, 2008; Weaver and Audsley, 2008; Huybrechts et al, 2010). No proctolin gene has been identified in genomes of Apis mellifera, Aedes aegypti, Bombyx mori, Nasonia vitripennis , or Acromymrex echinatior and three other ant species (see Roller et al, 2008; Hauser et al, 2010; Predel et al, 2010; Nygaard et al, 2011), where proctolin and its receptor are now considered absent.…”
Section: Introductionmentioning
confidence: 99%